Treatment Of Indian Visceral Leishmaniasis With Single Or Daily Infusions Of Low Dose Liposomal Amphotericin B: Randomised Trial - Sundar, Shyam; Agrawal, G.; Rai, Madhukar; Makharia, M. K.; Murray, Henry W. (BMJ (Online), 2001)
Objective To test short course, low dose liposomal amphotericin B as single or daily infusion treatment in Indian visceral leishmaniasis (kala-azar). Design Randomised, open label study. Setting Inpatient unit for leishmaniasis in Bihar, India. Participants 91 adults and children with splenic aspirate positive for infection. Interventions Total dose of 5 mg/kg of liposomal amphotericin B given as a single infusion (n = 46) or as once daily infusions of 1 mg/kg for five days (n = 45). Main outcome measures Clinical and parasitological cure assessed 14 days after treatment and long term definitive cure (healthy, no replase) at six months. Results All but one person in each group had an initial apparent cure. During six months of follow up, three patients in the single dose group and two in the five dose group relapsed. Complete response (definitive cure) was therefore achieved in 84 of 91 subjects (92%): 42 of 46 patients in the single dose group (91%, 95% confidence interval 79% to 98%) and 42 of 45 in the five dose group (93%, 82% to 99%). Response rates in the two groups were not significantly different. Conclusion Low dose liposomal amphotericin B (5 mg/kg), given either as a five day course or as a single infusion, seems to be effective for visceral leishmaniasis and warrants further testing.